CO2 – Intrinsic Product, Essential Substrate, and Regulatory Trigger of Microbial and Mammalian Production Processes - Blombach, Bastian; Takors, Ralf (Frontiers in Bioengineering and Biotechnology, 2015)
Carbon dioxide formation mirrors the final carbon oxidation steps of aerobic metabolism in microbial and mammalian cells. As a consequence CO2/HCO3- dissociation equilibria arise in fermenters by the growing culture. Anaplerotic reactions make use of the abundant CO2/HCO3- levels for refueling citric acid cycle demands and for enabling oxaloacetate derived products. At the same time CO2 is released manifold in metabolic reactions via decarboxylation activity. The levels of extracellular CO2/HCO3- depend on cellular activities and physical constraints such like hydrostatic pressures, aeration and the efficiency of mixing in large-scale bioreactors. Besides, local CO2/HCO3- levels might also act as metabolic inhibitors or transcriptional effectors triggering regulatory events inside the cells. This review gives an overview about fundamental physicochemical properties of CO2/HCO3- in microbial and mammalian cultures effecting cellular physiology, production processes, metabolic activity and transcriptional regulation.